Mönchtum als Stellvertretung? - Eckerstorfer, Bernhard A. (Zeitschrift für katholische Theologie, 2006)
This article explains the fundamental dynamic of religious life through the concept of representation as used in recent German theology. The contribution of monastic life to the world and the church is thus the cultivation of human life by means of representation, vicariate and intercession to the greater glory of God. In this way it mirrors the drama of salvation.